2017
DOI: 10.4274/tjod.15045
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal outcomes in pregnant women with hepatitis E infection; still an important fetomaternal killer with an unresolved mystery of increased virulence in pregnancy

Abstract: Objective:Hepatitis is a prevalent infection in developing countries. While hepatitis B and C are deepening their roots in the developed world, hepatitis A and E are common in the developing world. The uniqueness of hepatitis is in its transformation from a relatively self-limiting disease in the non-pregnant state, to a highly virulent disease during pregnancy.Materials and Methods:This retrospective observational study was conducted in the Department of Obstetrics and Gynecology, King George’s Medical Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
4
13
0
Order By: Relevance
“…In this study total 120 patients with hepatitis E were studied out of which nearly half of the patients had abnormal coagulation. This result is slightly higher than the result obtained from Kumar et al in which 31.2% had abnormal coagulation; however, it is lower than the study published by Patra et al in which 79% of cases had coagulopathies due to Hepatitis E. 7,8 The results of this present study are consistent with the studies published by Mishra et al and Badrakiya et al in which the percentage of patients with abnormal coagulation were 54.29% and 60% respectively. 9,11 Percentage of patients complicated with hepatic encephalopathy in this study was 28.3% which is found to be slightly higher to the studies published by Mishra et al, Kumar et al, and Badrakiya et al with their respective results as 20.95%, 21.8% and 15.4%.…”
Section: Maternal Morbiditysupporting
confidence: 84%
See 2 more Smart Citations
“…In this study total 120 patients with hepatitis E were studied out of which nearly half of the patients had abnormal coagulation. This result is slightly higher than the result obtained from Kumar et al in which 31.2% had abnormal coagulation; however, it is lower than the study published by Patra et al in which 79% of cases had coagulopathies due to Hepatitis E. 7,8 The results of this present study are consistent with the studies published by Mishra et al and Badrakiya et al in which the percentage of patients with abnormal coagulation were 54.29% and 60% respectively. 9,11 Percentage of patients complicated with hepatic encephalopathy in this study was 28.3% which is found to be slightly higher to the studies published by Mishra et al, Kumar et al, and Badrakiya et al with their respective results as 20.95%, 21.8% and 15.4%.…”
Section: Maternal Morbiditysupporting
confidence: 84%
“…Similar results have been seen in a study conducted by Kumar et al at King George Medical College, Lucknow wherein 90.63% patients delivered vaginally and 9.37% underwent lower segment caesarean section. 8 Also in the study by Badrakiya et al, 82% of pregnant patients with Hepatitis E had vaginal delivery while the percentage of caesarean section was 15.4%. 11 The inference from this analysis is that patients with hepatitis E go more often into spontaneous labour and deliver vaginally and less operative intervention is required.…”
Section: Mode Of Deliverymentioning
confidence: 94%
See 1 more Smart Citation
“…Screening forms for title and abstract screening, and full‐text screening were developed, piloted, and the screening questioned were adapted after piloting, before applied to the uploaded references. After screening of titles, abstracts and full texts, 21 references remained . Two additional studies were identified by checking references of included relevant papers .…”
Section: Resultsmentioning
confidence: 99%
“…The mean sample size was 58 (range 10‐148) with a total number of 1338 cases. Twelve studies had confirmed HEV diagnosis as an inclusion criteria, the rest had either jaundice, acute viral hepatitis or fulminant hepatic failure (FHF) as an inclusion criteria and tested for HEV later in the study. Most of the studies (20/23) had a follow‐up period that included delivery.…”
Section: Resultsmentioning
confidence: 99%